PENGARUH FREKUENSI PIJAT BAYI TERHADAP KUALITAS TIDUR BAYI USIA 1-3 BULAN DI MOMBYKIDS JOMBANG: Effect Of Baby Massage Frequency On Baby Sleep Quality 1-3 Months In Mombykids Jombang - Fera Yuli Setiyaningsih (Jurnal Ilmiah Kebidanan (Scientific Journal of Midwifery), 2019)
Sleep well is a need that must be solved by the baby because at this time sleep brain development reaches its peak. 51.3% of babies experience sleep disturbances, 42% of babies sleep less than 9 hours a night, and at night they wake up more than 3 times with an increase of more than one hour. This study discusses baby massage on sleep quality 1-3 months in mombykids. Research method: Design of the study used Case control study was conducted in November with a sample of 30 infants divided into two groups, namely the control group consisting of 15 infants, the report group consisted of 15 infants. The sampling technique uses total sampling. Data analysis using Chi Square. The results of the study: the results of Chi Square analysis p = 0.027 <0.05 so that it can be concluded related to infant massage with the quality of sleep for infants aged 1-3 months.